Caring for Sea Lamprey: Risk Management, Biotechnology, and Eradication in the Great Lakes - Gauthier, Noah (Université d'Ottawa / University of Ottawa, 2025)
CRISPR genome-editing technology offers great potential and considerable uncertainties for the future management of invasive sea lamprey (Petromyzon marinus) in the Laurentian Great Lakes. However, without the integration of CRISPR, the future of sea lamprey management is likely to mirror the past 70 years, characterized by significant maintenance and operational costs, ongoing chemical treatments in the water, and the continued use of barriers that block important migratory passages. This research examines the perspectives and potential of using CRISPR technology to control or eradicate sea lamprey in the Great Lakes, using the Great Lakes Fishery Commission's (GLFC) new genetic control theme as a case study. Fieldwork interviews in the Great Lakes region and virtual semi-structured interviews were conducted (n=16) with senior leadership from the GLFC, Indigenous Knowledge Holders and an Indian in Transition, First Nation Fishery Professionals, and scientists. A focus group (n=3) was also conducted with senior officials from the Government of Canada. The findings reveal that the use of CRISPR to control or eradicate sea lamprey in the Great Lakes is polarized, with significant opposition to applying CRISPR technology on host species. Additionally, the research identified that the current GLFC governance framework could be insufficient in meaningfully involving First Nations in the CRISPR decision-making process, which could potentially undermine Canadian law and community sovereignty. This research serves as a starting point for acknowledging the ethical conundrums associated with using CRISPR technology to control sea lamprey in the Great Lakes.
Keywords: CRISPR; sea lamprey; eradication; decision-making; sovereignty; technology